2020
DOI: 10.1097/md.0000000000018972
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and treatment of acute coronary syndrome as well as 1-year survival of patients hospitalized due to cancer

Abstract: The diagnosis of acute coronary syndrome (ACS) in patients with cancer constitutes a therapeutic challenge. We aimed to assess the clinical presentation and management of ACS as well as 1-year survival in patients hospitalized for cancer. This retrospective study included patients hospitalized between 2012 and 2018 in a nonacademic center. The inclusion criteria were diagnosis of active cancer and ACS recognized using standard criteria. Patients were assessed with respect to invasive or conservativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…When only ACS occurring during hospitalization for active cancer is considered, its incidence is lower. A retrospective analysis on 25,165 medical records of patients hospitalized to a Polish oncological center for cancer treatment reported an occurrence of ACS in 0.14% of patients [ 22 ]. Another retrospective analysis by Park et al [ 23 ], who screened 5300 patients with active hematologic malignancies, identified 73 cases (1.4%) of ACS (unstable angina in 8%, NSTEMI in 78% and STEMI in 14% of cases) during hospitalization for cancer.…”
Section: Prevalence and Clinical Characteristics Of Acs In Cancer mentioning
confidence: 99%
See 1 more Smart Citation
“…When only ACS occurring during hospitalization for active cancer is considered, its incidence is lower. A retrospective analysis on 25,165 medical records of patients hospitalized to a Polish oncological center for cancer treatment reported an occurrence of ACS in 0.14% of patients [ 22 ]. Another retrospective analysis by Park et al [ 23 ], who screened 5300 patients with active hematologic malignancies, identified 73 cases (1.4%) of ACS (unstable angina in 8%, NSTEMI in 78% and STEMI in 14% of cases) during hospitalization for cancer.…”
Section: Prevalence and Clinical Characteristics Of Acs In Cancer mentioning
confidence: 99%
“…Another retrospective analysis by Park et al [ 23 ], who screened 5300 patients with active hematologic malignancies, identified 73 cases (1.4%) of ACS (unstable angina in 8%, NSTEMI in 78% and STEMI in 14% of cases) during hospitalization for cancer. Although the incidence of ACS in patients hospitalized in oncological units with active cancer seems to be low, this represents a very high-risk group, characterized by in-hospital mortality rates of about 25% [ 22 , 23 ].…”
Section: Prevalence and Clinical Characteristics Of Acs In Cancer mentioning
confidence: 99%
“…However, recent studies [28,30,31] advocate that PCI + optimal medical therapy (OMT), especially acetylsalicylic acid use if not contraindicated, is associated with a better survival rate regardless of the cancer stage and/or eligibility for cancer treatment.…”
Section: Interventional Approachmentioning
confidence: 99%
“…Assessment of coronary stenosis with FFR is necessary before proceeding to PCI, as well as confirmation of excellent stent apposition after PCI with intravascular ultrasound (IVUS) or optical coherence tomography (OCT) [33]. OCT is recommended after stent placement to ensure optimal expansion, and an absence of complications may allow early DAPT interruption [25][26][27][28][29][30][31][32][33][34].…”
Section: Interventional Approachmentioning
confidence: 99%
“…В доступной литературе имеются единичные работы с описанием клинических особенностей течения ОКС в зависимости от наличия или отсутствия ОЗ, в том числе у лиц пожилого и старческого возраста, что еще раз подтверждает актуальность изучения данной проблемы [1,8,9].…”
unclassified